Sustainability of Oral History: A Case of SRK Pulo at Kampung Semarang (KEMANUSIAAN The Asian Journal of Humanities, 2024)
History is data regarding historical instances of human activity. This study anticipates the cultural memory around the primary school, SRK Pulo, which was relocated while retaining its previous name. One of the ancient Malay settlements along the Sarawak riverbank in Kuching is called Kampung Pulo. Questions are being asked about the SRK Pulo, its origin and other related histories to acknowledge. Further study, especially oral history inquiries, might help clear up any lingering questions regarding a historical truth or knowledge gap. For the benefit of future research, the cultural memory of intangible cultures needs to be preserved and documented through oral history research. To highlight historical local stories as the major focus in a qualitative manner, this study utilised Husserlism in Transcendental Phenomenology (TPh). The positive takeaways from oral history investigations into the genesis of SRK Pulo could serve as a guideline for the younger generation to respect and learn from the past to establish evocative living in the future. The sustainability of indigenous peoples in preserving their sociocultural ways of life and oral traditions depends on this study.